Penerapan Asuhan Keperawatan pada Ny. M. E. Dengan Asma Bronkial di RSUD Ende : - Nggeru, Yosefina Anggreni; Paschalia, Yustina; Sekunda, Maria Salestina; Doondori , Anatolia K. (Poltekkes Kemenkes Kupang, 2025)
According to Basic Health Research (RISKESDAS, 2018), the prevalence rate of asthma at all ages in Indonesia is 2.5%. The incidence of asthma is most common in the age group of 75 years and above and begins to decrease in the age group of 15-24 years. The role of nurses in providing nursing care to patients is by providing pharmacological therapy, non-pharmacology and providing education about bronchial asthma. In the implementation of nursing care in asthma cases, nurses are challenged or have problems with the lack of understanding of nurses about the use of literature in setting service standards such as having to use the Indonesia Nursing Diagnostic Standards (SDKI), Indonesia Nursing Output Standards (SLKI), Indonesia Nursing Intervention Standards (SIKI) and patient non-compliance in preventing asthma attacks. This case study aims to describe the nursing care of Mrs. M. E. with a medical diagnosis of bronchial asthma and analyze the gap between theory and real cases. The method used is a case study with a nursing care approach which includes review, diagnosis, planning, implementation and evaluation of nursing. The results of the case study found three nursing problems in the case, namely ineffective airway clearance related to airway hypersecretion, ineffective breathing patterns related to inhibition of breathing effort, and sleep pattern disorders related to shortness of breath. Nursing interventions and implementations are designed and implemented with dependent actions such as observation, education and interdependent such as collaborative actions. After 3 days of implementation, the problem of ineffective airway cleaning was partially resolved, and the problem of ineffective breathing patterns and sleep pattern disorders was resolved. After 3 days of implementation, the nursing problem of ineffective breathing patterns and sleep pattern disorders was resolved, while the problem of ineffective airway clearance was partially resolved and it was recommended for patients and families to follow all recommendations from health workers with the aim of preventing the onset of more severe complications